2012
DOI: 10.3389/fmicb.2012.00077
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in ammonia oxidizing communities across agricultural soils are driven by soil structure and pH

Abstract: The milieu in soil in which microorganisms dwell is never constant. Conditions such as temperature, water availability, pH and nutrients frequently change, impacting the overall functioning of the soil system. To understand the effects of such factors on soil functioning, proxies (indicators) of soil function are needed that, in a sensitive manner, reveal normal amplitude of variation. Thus, the so-called normal operating range (NOR) of soil can be defined. In this study we determined different components of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 75 publications
3
23
0
1
Order By: Relevance
“…Sandy loam soil (soil-water pH 5.04) was collected from the top 15 cm of a well-characterized agricultural field in Buinen, The Netherlands (52°55′N, 6°49′E) from four (2 × 2 m) plots in April 20133839. Following collection, soils were homogenized by sieving through a 4 mm sieve, moisture was adjusted to 65% water holding capacity (~58% in the field) with sterile water, and soils were allowed to stabilize for one month at 4 °C before filling the microcosms.…”
Section: Methodsmentioning
confidence: 99%
“…Sandy loam soil (soil-water pH 5.04) was collected from the top 15 cm of a well-characterized agricultural field in Buinen, The Netherlands (52°55′N, 6°49′E) from four (2 × 2 m) plots in April 20133839. Following collection, soils were homogenized by sieving through a 4 mm sieve, moisture was adjusted to 65% water holding capacity (~58% in the field) with sterile water, and soils were allowed to stabilize for one month at 4 °C before filling the microcosms.…”
Section: Methodsmentioning
confidence: 99%
“…Here, stability arises because the dynamics of the diverse systems are less dependent on individual species. This is particularly important in soils, which exhibit a very high species turnover rate: in one case, the bacterial and archaeal ammonia oxidizing communities in a range of Dutch agricultural soils showed above 50% change in community structure between seasons [61,62]. In another, it was shown that when colonizing a novel environment, the microbial community undergoes drastic rearrangement, and draws heavily from members of the 'rare biosphere' [9,63], a strategy which may be crucial for stressresponse [51].…”
Section: Long-term Effects: Stability and Resiliencementioning
confidence: 99%
“…Microbial gene abundance did not differ between sorghum crop and grassland soils, but was generally lower in switchgrass soils as compared to nearby grassland soils. The differences we observed in soil chemistry and microbial communities are likely linked to differences in land use, agronomic practices, and soil type [37][38][39][40][41][42]. Higher macronutrient levels in the sorghum sites than nearby grassland sites are likely the result of fertilizer additions during cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Using the GeoChip FGA approach, which is based on DNA probes for functional microbial genes rather than for specific taxa, we observed some significant differences among the N cycling genes for nitrogen fixation, nitrification, and denitrification. In addition to the known effects of N fertilization on soil microbial communities [46][47][48][49], other factors reported to influence microbial composition and activities in soils include plant species and genotype, soil type, soil structure and pH, and the interactions and feedback between plants and soils [37][38][39][40][41][42]. Use of the GeoChip 4.0 allowed us to look for microbial gene diversity and abundance differences among diverse geographic samples across multiple gene categories that related to important ecosystem processes such as C, N, P, and S cycling.…”
Section: Ecological Implicationsmentioning
confidence: 99%